The next generation virus‐like particle platform for the treatment of peanut allergy - Sobczak, Jan M.; Krenger, Pascal S.; Storni, Federico; Mohsen, Mona O.; Balke, Ina; Reseviča, Gunta; Heath, Matthew D.; Carreno Velazquez, Thalia L.; Kramer, Matthias F.; Scott, Callum J. W.; Skinner, Murray A.; Zeltiņš, Andris; et al. (Allergy (Copenhagen), 2023)
Background Allergy to peanut is one of the leading causes of anaphylactic reactions among food allergic patients. Immunization against peanut allergy with a safe and protective vaccine holds a promise to induce durable protection against anaphylaxis caused by exposure to peanut. A novel vaccine candidate (VLP Peanut), based on virus‐like particles (VLPs), is described here for the treatment of peanut allergy. Methods and Results VLP Peanut consists of two proteins: a capsid subunit derived from Cucumber mosaic virus engineered with a universal T‐cell epitope (CuMVTT) and a CuMVTT subunit fused with peanut allergen Ara h 2 (CuMVTT‐Ara h 2), forming mosaic VLPs. Immunizations with VLP Peanut in both naïve and peanut‐sensitized mice resulted in a significant anti‐Ara h 2 IgG response. Local and systemic protection induced by VLP Peanut were established in mouse models for peanut allergy following prophylactic, therapeutic, and passive immunizations. Inhibition of FcγRIIb function resulted in a loss of protection, confirming the crucial role of the receptor in conferring cross protection against peanut allergens other than Ara h 2. Conclusion VLP Peanut can be delivered to peanut‐sensitized mice without triggering allergic reactions, while remaining highly immunogenic and offering protection against all peanut allergens. In addition, vaccination ablates allergic symptoms upon allergen challenge. Moreover, the prophylactic immunization setting conferred the protection against subsequent peanut‐induced anaphylaxis, showing the potential for preventive vaccination. This highlights the effectiveness of VLP Peanut as a prospective break‐through immunotherapy vaccine candidate toward peanut allergy. VLP Peanut has now entered clinical development with the study PROTECT. The vaccine candidate against peanut allergy described in the study consists of peanut allergen Ara h 2 genetically fused to the VLP subunits, which precludes the presence of free allergen in the vaccine formulation. We demonstrate the vaccine‐induced protection of peanut‐sensitized mice after the therapeutic treatment and in the prophylactic regimen. Thus, the here described VLP can be a potential breakthrough therapy for peanut allergy.Abbreviations: CuMVTT, Cucumber mosaic virus‐derived VLPs engineered with a universal T cell epitope; IgG, Immunoglobulin G; pETDuet‐1, bacterial vector for the co‐expression of two genes; VLP, virus‐like particle